Enhancing Public Service Delivery and Citizen Participation: The Synergistic Effects of E- Governance and Social Media - Asadon, Ma. Francisca A.; Brucal, Alyssa P.; Claveria, Pia Sarah L.; Lacson, Jan Tracey N.; Malang, Bernandino P.; Malang, Jocelyn DS. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study investigates the effects of social media and e-governance on public service delivery and citizen engagement in the Philippines. It is based on the idea that digital technology can enhance the efficiency, transparency, and trustworthiness of government, thus using the Unified Theory of Acceptance and Use of Technology (UTAUT2) to identify key factors driving adoption among citizens and government bodies. E-governance decreases the costs, errors, and delay in service delivery among Laguna residents, according to data from a survey. Public participation is enhanced by social media with more satisfaction and trust than other traditional media. Together, these tools improve the responsiveness of public policy and effectiveness to the public. Challenges such as infrastructural limitation, digital resistance, and privacy concerns have however been facing full adoption. Policymakers should remove the above barriers to ensure a totally realized benefit of digital governance for a more transparent, efficient, and participatory government.